The Sales and Competitive Effects of Styling and Advertising Practices in the U.S. Auto Industry - Kwoka, John E. (The Review of Economics and Statistics, 1993)
This paper utilizes a detailed data set on most U.S. car models over a twenty-two-year period to determine the impact of advertising and product styling. It finds that, while advertising and style change each increases a model's sales, advertising is short-lived but styling has a much longer impact. Rivals' styling reduces own-model sales to the point that the overall market effect is self-canceling. Rivals' advertising, by contrast, does not greatly affect own sales, so that marketwide advertising does increase total sales. These results add several twists to previous analyses of this industry. Copyright 1993 by MIT Press.